Pembuatan Minyak Atsiri dari Komoditas Alam Daun Kayu Putih - Al'farisi, Cory Dian; Zahrina, Ida; Drastinawati, Drastinawati; Khairat, Khairat; Herman, Syamsu; Utami, Anggia Afza; Alfajar, Fariz (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2024)
Eucalyptus oil is one of the essential oil obtained from the extraction of eucalyptus leaves. The purpose of this study is to evaluate the effect of variations in sample treatment and extraction time on the yield of eucalyptus essential oil and determine the characteristics of eucalyptus essential oil produced by the hydro distillation method. Variations in sample treatment were carried out by chopping, crushing, and blending dry eucalyptus leaves. 500 grams eucalyptus leaves are weighed and put in a 2000 mL flask. ±1000 mL of distilled water was added and the extraction process was carried out for 5, 6 and 7 hours. The results showed that the highest yield was obtained from blending treatment with an extraction time of 7 hours with a yield of 0.58%. Characteristic tests on eucalyptus leaf essential oil included: color, odor, specific gravity, refractive index and solubility in ethanol 80%. From the analysis of the test results, the color of eucalyptus oil is cloudy. The odor test results obtained are the distinctive odor of eucalyptus. The best value of eucalyptus oil specific gravity was 0.913 on crushed leaves for 6 hours. In the ethanol solubility test, the resulting oil dissolves in ethanol and a clear solution is obtained. The highest refractive index value of eucalyptus oil on chopped leaves for 5 hours is 1.469. Eucalyptus oil has a quality in accordance with the quality requirements of SNI 3954: 2014.